Functional assessment of various rare-earth (RE) ion types: An investigation on gamma-ray attenuation properties of GeO2-B2O3-P2O5-ZnO-Tb2O3-RE magneto-optical glasses - ALMisned, Ghada; Şen Baykal, Duygu; Ilik, E.; Abuzaid, Mohammed; Kılıç, Gökhan; Tekin, H. O. (My University, 2023)
We report the functional assessment of various rare-earth (RE) ion types on gamma-ray attenu- ation properties of GeO2-B2O3-P2O5-ZnO-Tb2O3-RE (where; RE=0; 1 %Ho, 1 %Pr, 1 %Er, 1 %Nd, 1 %Dy, 1 %Ce) magneto-optical glasses. The elemental fractions and densities of each glass sample were specified separately for the MCNPX Monte Carlo code. In addition to fundamental gamma absorption properties, Transmission Factors throughout a broad radioisotope energy range were measured. According to findings, Holmium (Ho) incorporation into the glass structure resulted in a net increase of 0.3406 g/cm3, whereas Cerium (Ce) addition resulted in a net in- crease of 0.2047 g/cm3. The Ho-doped S2 sample was found to have the greatest LAC value, despite the fact that seven glass samples exhibited identical behavior. The Ho-doped S2 sample had the lowest HVL values among the glass groups evaluated in this work, computed in the energy range of 0.015–15 MeV. The lowest EBF and EABF values were reported for Ho reinforced S2 sample with the highes LAC and density values. For all glass samples, a decrease in TF values was observed depending on the increase in thickness. Among the investigated glasses, Ho and Er reinforced samples (i.e., S2 and S4) showed the minimum TF values at used radioisotope energies. It can be concluded that Ho and Er type rare earth elements may provide the most effective gamma ray absorption properties when they are incorporated into the GeO2-B2O3-P2O5-ZnO- Tb2O3 system
Keywords: Rare-earth ions; Glasses; MCNPX; Transmission factor; Shielding